Prevalence and associated factors for needlestick and sharp injuries (NSIs) among dental assistants in Jeddah, Saudi Arabia - Lama AlDakhil; Nagarajkumar Yenugadhati; Ohoud Al-Seraihi; Mustafa Al-Zoughool (Komiyama Printing Co. Ltd, 2019)
Abstract Background Dental personnel are subject to exposure to a number of occupational factors including needlestick and sharp injuries (NSIs). Our study aims to address knowledge gaps on prevalence and associated factors for needlestick and sharp injuries (NSIs) for the first time in Saudi Arabia. Methods This cross-sectional study was conducted on a sample of 450 dental assistants recruited from 40 randomly selected private clinics in Jeddah, Saudi Arabia. Data on demographic characteristics, history of NSIs, nature of work, compliance with infection control protocols, and knowledge of infection control procedures and disease transmission were collected using a self-administered questionnaire. Logistic regression analysis was used to assess factors associated with NSIs; unadjusted and adjusted odds ratios (aORs) and their respective 95% confidence intervals (CIs) were computed. Results About three in ten dental assistants experienced at least one NSI (29.8%, 95% CI 25.6-34.2%) in private dental clinics. Lack of adequate knowledge of infection control procedures and disease transmission, non-compliance with infection control protocol of vaccination against hepatitis B virus, and attending 12 or less number of patients daily were significantly associated with increased risk of NSIs (p ≤ 0.05); adjusted odds ratios (95% CI) were 1.87 (1.18-2.97), 1.89 (1.05-3.41), and 1.63 (1.03-2.56), respectively. In addition, dental assistants working in 45.8% of dental clinics that had no infection control unit were positively associated with higher NSI risk (aOR = 2.28, 95% CI 1.45-3.57). Conclusion Our study reported the prevalent nature of NSIs among dental assistants in Saudi Arabia and identified key factors that could be targeted to mitigate this preventable condition. Dental assistants would benefit from proper training on infection control protocols and procedures.